Lithium and osmium isotopes, and trace element ratios in bulk carbonates of different ODP Sites across the Middle Eocene Climatic Optimum - Krause, Alexander; Sluijs, Appy; Van der Ploeg, Robin; Lenton, Timothy M; Pogge von Strandmann, Philip A E (PANGAEA, 2023)
The Middle Eocene Climatic Optimum (MECO) was a ~400,000-year-long global warming event which occurred ~40 million years ago and interrupted the Eocene's long-term cooling trend. We investigated silicate weathering dynamics during the MECO by measuring lithium isotope ratios and elemental ratios (Li/Ca, Al/Ca, Mn/Ca, Sr/Ca, Rb/Ca) from a suite of open-ocean carbonate-rich sediments.
Keywords: Clay formation; Climate changes; Congruent weathering; Lithium isotopes; MECO; Middle Eocene Climatic Optimum; reverse weathering; Silicate weathering